Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Dana Bagi Hasil terhadap Belanja Modal pada Daerah Pemekaran di Provinsi Jambi - Amelia Agustin (Universitas Batanghari Jambi, 2021)
Local taxes are the obligation of citizens to finance various regional needs to carry out regional development. This is an important benchmark for contributing to increasing local revenue in implementing regional autonomy. This study aims to determine how much the contribution of provincial taxes in increasing local revenue (PAD) in Jambi province. Based on the result of the analysis contribution and Analysis Process Hierarchy (AHP), get the results of the research in the form that of the five (5) province taxes that greatly contribute to increasing local revenue, namely Motor Vehicle Tax, Motor Vehicle Transfer Fee Tax and Motor Vehicle Fuel Tax. These three taxes greatly contribute, which for motor vehicle taxes in 2017-2019 or the last 3 years can contribute 27.91%, motor vehicle transfer fees tax contributes 22.67% and motor vehicle fuel taxes contribute 19.39 % . Meanwhile, the other two taxes, the surface water tax and the cigarette tax, began to contribute to local revenue (PAD), although their contribution was not very large.